A 22‐Year Follow‐Up (Range 16 to 23) of Original Subjects with Baseline Alcohol Use Disorders from the Collaborative Study on Genetics of Alcoholism. (5th July 2018) - Schuckit, Marc A.; Smith, Tom L.; Danko, George; Kramer, John; Bucholz, Kathleen K.; McCutcheon, Vivia; Chan, Grace; Kuperman, Samuel; Hesselbrock, Victor; Dick, Danielle M.; Hesselbrock, Michie; Porjesz, Bernice; et al.
Abstract : Background: Recent reports indicate higher‐than‐expected problematic drinking in older populations. However, few data describe how to predict which older individuals are most likely to demonstrate alcohol‐related problems, including those with earlier alcohol use disorders (AUDs). These analyses evaluate predictors of alcohol outcomes in individuals with earlier AUDs in the Collaborative Study on Genetics of Alcoholism (COGA). Methods: Original COGA participants with baseline AUDs at about age 40 were interviewed 13 to 26 years later and placed into clinically derived outcome categories. Chi‐square and analysis of variance evaluated baseline differences across 4 outcome groups, with significant items entered into binary logistic regression backwards elimination analyses predicting outcomes. Results: Low‐Risk Drinkers ( N  = 100) at follow‐up were predicted by baseline higher levels of response to alcohol (high LRs), lower histories of alcohol treatment, experience with fewer types of illicit drugs, and were more likely to have been widowed. At follow‐up, Problem Drinkers ( N  = 192) differed from High‐Risk Drinkers ( N  = 93) who denied multiple alcohol problems by exhibiting baseline lower LRs, higher Sensation Seeking, and a higher proportion who were widowed. Abstinent ( N  = 278) outcomes were predicted by a history of higher baseline AUD treatments, higher alcohol problems, lower usual drinks, as well as older age and European American heritage. Thirty‐four subjects (4.9%) could not be classified and were not included in these analyses. Conclusions: These results generated from AUD individuals from both treatment and nontreatment settings reinforce low probabilities of recent Low‐Risk Drinking in individuals with AUDs, but also suggest many individuals with AUDs demonstrate good outcomes 2 decades later. Abstract : Alcohol use disorders (AUDs) carry enhanced early death risks, but few studies evaluated predictors of long‐term outcomes in survivors. In this 22‐year investigation of 663 AUD individuals, 15% maintained recent low risk drinking, 43% had problematic or excessive drinking, and 42% had prior year abstinence. These data can help clinicians educate older AUD patients about long‐term outcomes and to intervene more robustly in those with worse prognoses.